EFEKTIVITAS PROGRAM PENDATAAN KELUARGA DI KOTA PEKANBARU OLEH BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) PERWAKILAN PROVINSI RIAU TAHUN 2015 - Muhammad Affandi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Family Data Collection in 2015 is the primary data collection activities on the data of Population, Family Planning Data, Data Family Development (KKBPK) in Pekanbaru conducted by the National Population and Family Planning (BKKBN) Representatives of the Province of Riau. For the expected availability of the database, it must be ensured all families recorded. Implementation of this program up and running no less effective because of the level of community participation Pekanbaru City is still low and still many shortcomings of the Agency of National Population and Family Planning (BKKBN) Representatives of Riau Province as program implementers.This study used a qualitative approach, this kind of research is a descriptive study. The focus of research is the effective implementation of the program and community participation. Informant in this study is the Head of Public Affairs and Public Relations of the Agency of National Population and Family Planning (BKKBN) Representatives of the Province of Riau, Chairman Validator of the Family Data Collection Data 2015, and 12 family heads. Data collection techniques in this study using observation, interviews . Data analysis techniques used in this research is descriptive analysis techniques.The results of this study show implementation of the program has not been effective, coupled with the apathy of people in Pekanbaru is still high. recommendation for this research is reassure the public about the active participation in the government program, communication between the government and the public, or otherwise to enable the development of society and the government should more leverage in implementing the program in order to run effectively and optimally.Keywords: Family Data Collection In 2015, Effectiveness, Public Participation